21st International Congress on Anticancer Treatment. Issue 5 (May 2010) - Magnéé, Nicolas; Pacaut, Céécile; Chargari, Cyrus
The 21st International Congress on Anticancer Treatment, endorsed by the American Society of Clinical Oncology, was held in Paris (France) 1––5 February 2010. It was led and jointly sponsored by Gabriel Hortobagyi and David Khayat and by the University of Texas MD Anderson Cancer Center (TX, USA) and the Hôôpital de la Pitiéé Salpêêtrièère (Paris, France), respectively. The meeting provided complete updates and innovations in the management of various cancers and supportive care. This well-recognized annual international educational and scientific conference brought together the leading scientists from across the world to share their skills and expertise by participating in this high-quality meeting. This congress provides an exceptional opportunity to meet with fellow professionals and discuss new educational case studies. In the present article, we have highlighted particularly pertinent sessions concerning hot topics for the new areas of cancer.